Податковий сертифікат - фінансова альтернатива стратегічного розвитку оподаткування на місцевому рівні - Кучерова, Г.Ю. (Вісник економічної науки України, 2016)
В статті здійснено спробу обґрунтування доцільності впровадження в обіг податкових сертифікатів в Україні. Узагальнено основні етапи розвитку податку на нерухоме майно, відмінне від земельної ділянки, в Україні. Проаналізовано механізм майнового оподаткування в США. Охарактеризовано механізм управління податковими боргами з оплати податку на майно в США, що базується на використанні механізму формування та реалізації податкових сертифікатів, які дають змогу максимально швидкого поповнити їх бюджети, стимулювати платників податків до дотримання податкової дисципліни та підвищити рівень ліквідності активів. Визначено значний потенціал механізму формування та реалізації податкових сертифікатів щодо формування додаткових надходжень місцевих бюджетів в Україні. В статье предпринята попытка обоснования целесообразности внедрения в оборот налоговых сертификатов в Украине. Обобщены основные этапы развития налога на недвижимое имущество, отличное от земельного участка, в Украине. Проанализирован механизм имущественного налогообложения в США. Охарактеризовано механизм управления налоговыми долгами по оплате налога на имущество в США, основанный на использовании налоговых сертификатов, которые позволяют максимально быстрого пополнить их бюджеты, стимулировать налогоплательщиков к соблюдению налоговой дисциплины и повысить уровень ликвидности активов. Определено значительный потенциал механизма налоговых сертификатов по формированию дополнительных поступлений в местные бюджеты в Украине. An attempt to ground expediency of introduction in an appeal in Ukraine of tax certificates is undertaken in the article. For realization the set problem the basic stages of development of tax are generalized property different from lot land, that confirmed dynamic quality of his transformations and actualization only in the last few years. Also, his fiscal meaningfulness and growing potential are well-proven. The mechanism of property taxation is analyses in the USA and a fundamental difference is educed as compared to Ukraine, that consists in that a home tax on property ties down to the indexes of profits of taxpayers, but not market value of property. Management mechanism by tax debts on a tax on property in the USA is based on the use of tax certificates, that allows to municipalities of the states maximally rapid to fill their budgets, stimulate taxpayers to the observance of tax discipline and promote the level of liquidity of assets. The mechanism of the use of tax certificates is studied in the USA, it is set as a result, that an investor that purchased a tax certificate and discharged debts on payment of taxes in a budget takes title to exact overdue taxes, fine and percents for ill-timed tax from a debtor, the bag of that in the USA can make from 12% to 36% annual depending on the state of property, payment, here the potential profit of investor makes from 4-7% from a transaction. Thus, the examined tax certificate has considerable potential on forming of additional receivables of local budgets in Ukraine, therefore requires a further study and research.